Perioperative high-dose amiodarone elevates nitric oxide levels in patients undergoing coronary artery bypass surgery - Uysal, Ayhan; Azak, Soner; Colak, M.Cengiz; Burma, Oktay; Ozguler, I. Murat; Ustundag, Bilal; Bayar, Mustafa Kemal (My University, 2013)
The aim of the current study was to assess the effects of the Class III antiarrhythmic drug amiodarone on arterial blood Nitric oxide (NO) levels together with malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-px), and catalase (CAT) levels in patients undergoing coronary artery bypass surgery (CABG). Twenty patients undergoing CABG were included in the study. The patients were divided into control and amiodarone groups (n=10 in each group). The patients in group 1 did not receive any drugs. The patients in group II received 4X400 mg/day amiodarone on the day before surgery, 2X600 mg/day amiodarone on the day of surgery, and 2X400 mg/day amiodarone for the first consecutive four days after the surgery. NO, MDA, SOD, GSH-px, and CAT values were measured for biochemical evaluation of oxidative stress before the induction of anesthesia (TA), before CPB (TCPB), five minutes after the clamp was removed (Tc), after pro-tamine (TP), and on postoperative days 1 (T1), 3 (T3), and 5 (T5). Hemodynamic changes of all patients were recorded at before the induction of anesthesia (TA), before CPB (TCPB), after protamine (TP), and on postoperative day 1 (T1). Amiodarone elevated NO levels at all times during the study period but did not cause changes in MDA, SOD, GSH-px, or CAT. In addition, amiodarone decreased mean pulmonary artery pressure, pulmonary capillary wedge pressure, and heart rate in these patients. No side effect due to drug was observed. Heart rate was found more decreased in amiodarone group at T1 and T2 stages when compared with controls (p<0.05). Perioperative high-dose amiodarone might be beneficial for patients who are pulmonary hypertensive and are undergoing CABG.
Keywords: Amiodarone; Coronary bypass surgery; Nitric oxide